2012
DOI: 10.1142/s0192415x12500668
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Japanese Herbal (Kampo) Medicines and Treatment of Ocular Diseases: A Review

Abstract: Herbal medicines have been used clinically in Eastern Asia, and traditional Japanese herbal (Kampo) formulas are approved as ethical drugs. The Kampo formulas are mixtures of the crude extracts of several herbs, each of which contains multiple components. Numerous investigators have reported that some herbal medicines are efficacious for treating several human diseases. We reviewed the literature on traditional herbal medicines and treatment of ocular diseases. Oral Orengedoku-to and Kakkon-to inhibit postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Kampo medical formulas have been used to treat a variety of physical illnesses and diseases [5], including ocular conditions such as dry eye, blurred vision, decreased visual acuity, and visual field defects [6]. However, the clinical efficacy of kampo medicine has traditionally been evaluated with subjective assessments of symptoms, and there is little quantitative information on the effects of kampo medical formulas on the eye [7]. A few such studies have suggested that yokukansan (YKS) has an influence on blood flow in the short posterior ciliary artery in rabbits [8] and that hachimijiogan (HJG) has an effect on blood flow in the central retinal artery in humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kampo medical formulas have been used to treat a variety of physical illnesses and diseases [5], including ocular conditions such as dry eye, blurred vision, decreased visual acuity, and visual field defects [6]. However, the clinical efficacy of kampo medicine has traditionally been evaluated with subjective assessments of symptoms, and there is little quantitative information on the effects of kampo medical formulas on the eye [7]. A few such studies have suggested that yokukansan (YKS) has an influence on blood flow in the short posterior ciliary artery in rabbits [8] and that hachimijiogan (HJG) has an effect on blood flow in the central retinal artery in humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence that herbal extracts have been found attractive in controlling diabetes with little toxicity. [7][8][9] This present study was therefore performed to validate our hypothesis for the anti-diabetic potential of EOPK, based on our previous report on the anti-hyperlipidemic effect 16) of EOPK, since the metabolic syndrome includes obesity, diabetes and hyperlipidemia. There are the two species of Pinus calorpreferens and Pinus glomerata from Pinus koraiensis in Korea, 19) and Yang et al have identified the presence of the eight compounds, 8(14)-podocarpen-13-on-18-oic acid, 15-hydroxydehydroabietic acid, 12-hydroxyabietic acid, lambertianic acid, dehydroabietic acid, sandaracopimaric acid, -sitosterol and daucosterol.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Recent hypoglycemic herbal medicines are therefore considered attractive, since they are suitable for long-term diabetes control with little toxicity. 7,8) The chloroform fraction of Andrographis paniculata has recently exerted an anti-diabetic effect on diabetic albino mice, 9) a cinnamon extract has shown a moderate effect in reducing the fasting plasma glucose concentration in diabetic patients with poor glycaemic control, 10,11) and a curcumin extract has improved the overall function of -cells from T2DM patients with very minor adverse effects. [12][13][14][15] The metabolic syndrome includes obesity, hyperlipidemia and diabetes, and we can hypothesize on the anti-diabetic potential of EOPK, given that our previous study has shown the essential oil from leaves of Pinus koraiensis (EOPK) to exert its antihyperlipidemic effects by upregulating the low-density lipoprotein receptor and inhibiting cholesterol acyltransferases.…”
mentioning
confidence: 99%
“…Oral Gosha-jinki-gan improved ocular surface disorders in patients with type 1 diabetes mellitus, while oral Hachimi-jio-gan increased retinal blood fl ow. Topical glycyrrhizinate improved allergic conjunctivitis in humans, and oral crocetin is reported to improve eyestrain in humans (Hayasaka et al 2012 ).…”
Section: Polyherbal Formulations and Methods From Alternative Systemsmentioning
confidence: 99%